2012 TC4 - An unusual fast-rotating PHA with C-type taxonomy. (February 2019) - Lin, Zhong-Yi; Ip, Wing-Huen; Ngeow, Chow-Choong
Abstract: The potentially hazardous asteroid 2012 TC4 made an Earth close approach at a distance of 0.11 lunar distance on 12 October 2017. Photometric observations were carried out between October 11 and October 12 at the Lulin Observatory at short cadence. Data analysis of the light curves shows that this PHA has a fast rotation period of 12.25 min, a light curve variation amplitude of 1.2 ± 0.1 mag corresponding to an axial ratio of about 3.0. Our BVRI photometry also indicates that 2012 TC4 is a C-type asteroid. With the C-type albedo of 0.065 and an absolute magnitude of H = 26.613 ± 0.350, its effective diameter can be derived to be 24.8 − 8.0 + 19.1 m.